MOTIVASI AUSTRALIA MEMBERIKAN BANTUAN PENDIDIKAN KEPADA MADRASAH DI INDONESIA MELALUI PROGRAM AUSAID TAHUN 2011-2014 - Bella Risasta; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This paper aims to explain the motivation of Australia in providing foreign aid, especially aid to Indonesia in Islamic education sub-sector. Australia provides assistance to Indonesia through the International donor agencies namely Australia Agency for International Development (AusAID), which is currently under arrangements Ministry Foreign Affairs and Trade of Australia. Through AusAID, Australia has provided assistance to the sub-sectors of madrasa education in the form of block grants and training assistance in order to improve the quality and the quality of the madrasah.This study uses the perspective of realism where realism view that foreign aid is one of the tools of diplomacy when there is a state interest which cannot be achieved only by using military force. This paper also uses a combination of public diplomacy theory and the concept of soft power at the level of the nation state analysis.The results from this study consider that Australia provides assistance to sub-sector madrasa education with the aim to dampen radicalism in madrassas. This can be seen from the formulation aid that began after the Bali bombing and the provision which requires madrassas should be tolerant, open and willing to instill the value of pluralism.Keywords: Foreign Assistance, Education Assistance, AusAID, Radicalism, Madrasa Education Sub-Sector, Education Partnership.